Students’ Perceptions of Internalizing Local Cultural Accommodation Values in Religious Moderation - Yudi Gucandra; Novi Hendri; Riri Susanti (STIT Ahlussunnah Bukittinggi, 2026)
This study aims to describe the perceptions of sixth-semester students in the Islamic Religious Education Program toward the internalization of local cultural accommodative values in religious moderation. The accommodative dimension remains one of the least empirically explored aspects compared to other dimensions of religious moderation. This study employed a descriptive quantitative approach using a survey method. The sample consisted of 80 students selected from a total population of 400 sixth-semester students through stratified random sampling. The research instrument was a Likert-scale questionnaire ranging from 1 to 5, developed based on four sub-indicators: recognition of cultural diversity, appreciation of local traditions, integration of Islam and culture, and cross-ethnic inclusive attitudes. The data were analyzed using descriptive statistics. The findings revealed that the average perception score reached 4.47 out of 5, which falls into the very high category. The recognition of cultural diversity sub-indicator obtained the highest score, while cross-ethnic inclusive attitudes received the lowest score. These findings indicate a tendency toward a gap between cognitive understanding and behavioral implementation in religious moderation. The study concludes that the learning process has successfully internalized local cultural accommodative values at a very high level; however, strengthening the behavioral dimension through more structured cross-cultural practices remains necessary.